Hegel, Nietzsche, and philosophy : thinking freedom - Dudley, Will, 1967- (Modern European philosophy., 2002)
This study explores the theme of freedom in the philosophy of Hegel and Nietzsche. In bringing Hegel and Nietzsche together into a conversation, Will Dudley has developed some original interpretations that will be of considerable importance to students of these philosophers, and to political theorists and historians of ideas.